2018
DOI: 10.1049/iet-nbt.2017.0263
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of AgNPs by B. maydis and its antifungal effect against Exserohilum turcicum

Abstract: In the present study, was used to synthesise silver nanoparticles (AgNPs). Several parameters that influence the synthesis of AgNPs such as fungus age, the concentration of Ag nitrate (AgNO), and incubation time were explored to find the optimum synthesis condition. Furthermore, the antifungal activity of AgNPs against was determined by measuring inhibition zone diameter, colony formation, and conidia germination. The optimal biosynthesis system included fungus age of 7 days, 8 mM AgNO, and an incubation time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…According to the literature, the absorption peaks between 380–450 nm are related to the surface plasmon resonance (SPR) of silver nanoparticles ( Desai et al, 2012 ; Mistry et al, 2021 ). Our UV–Vis results corroborate with those presented by Huang et al (2018) and Osorio-Echavarría et al (2021) who showed that AgNPs synthesized from fungi releveled strong peaks at 430 nm.…”
Section: Discussionsupporting
confidence: 92%
“…According to the literature, the absorption peaks between 380–450 nm are related to the surface plasmon resonance (SPR) of silver nanoparticles ( Desai et al, 2012 ; Mistry et al, 2021 ). Our UV–Vis results corroborate with those presented by Huang et al (2018) and Osorio-Echavarría et al (2021) who showed that AgNPs synthesized from fungi releveled strong peaks at 430 nm.…”
Section: Discussionsupporting
confidence: 92%
“…These hydrophilic interactions mediated the arrangement of AgNPs@BB extracts into spherical assemblies to increase their size and serve as templates. Therefore, conjugates of AgNPs with peptide oligomers not only bring about the formation of aggregates, but also have a role in controlling their morphology [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in vivo studies depicted that TiO 2 nanoparticles increased cardiac conduction velocity and tissue excitability, resulting in an enhanced propensity for inducible arrhythmias [ 192 ]. An antifungal effect of representative nanoparticles is summarized in Table 1 [ 136 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 ].…”
Section: Carbon Nanoparticlesmentioning
confidence: 99%